The impact of using the MAE (online banking) application among Maybank Kuala Krai customers / Ahmad Husaini Abd Karim - Abd Karim, Ahmad Husaini (2025)
This study was conducted to assess the impact of using the MAE (Maybank Anytime Everyone) application among Maybank Kuala Krai customers by focusing on three main objectives. The first objective was to assess the level of customer satisfaction with the facilities provided by the MAE application, which facilitates daily banking transactions such as money transfers, bill payments, and account management. The second objective was to identify the level of customer acceptance of Islamic banking products offered through this application, such as Savings Account-i and sharia-compliant investments, which reflect Maybank's commitment to Islamic banking principles. The third objective was to analyze the impact of using the MAE application on customers' personal financial management, including their ability to monitor spending, manage savings, and improve financial literacy. This study used a quantitative approach with a questionnaire as the data collection instrument, involving respondents from Maybank customers in Kuala Krai. The results of the study showed that most customers were very satisfied with the facilities provided by the MAE application, especially in terms of user-friendliness and time efficiency. Furthermore, the level of customer acceptance of Islamic banking products was high, driven by their confidence in the sharia-compliance of the products. Further analysis found that the use of the MAE application had a positive impact on customers' personal financial management, especially in terms of real-time expense monitoring, more organized financial planning, and the convenience of saving money regularly. Overall, the findings of this study indicate that the MAE application not only enhances customers' banking experience but also plays an important role in helping customers manage their finances more effectively. The implications of the study suggest that Maybank needs to continue to improve the features of the MAE application to meet customer needs, including expanding its Islamic banking product offerings and providing financial literacy guidance through the application platform. This study also provides the potential of mobile banking applications as an important tool to promote better financial management among the community, in line with the development of digital technology in the financial sector.